(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Anthropometric indicators play a vital role in assessing the health and well-being of children. These indicators provide valuable information about a child’s physical growth and development, helping healthcare professionals, parents, and policymakers to monitor their overall health status. The purpose of this article is to explore the significance of anthropometric indicators in children’s health and well-being and to highlight their importance in identifying growth disorders, malnutrition, and other health conditions. By understanding and interpreting these indicators correctly, we can ensure the optimal growth and development of children, promoting their long-term health and well-being.